Capacity market in the decarbonization era: Adequacy, flexibility, and environmental revenue - Chaojie Li; Youquan Jiang; Jiang Dai; Ruyue Guo; Ying Zhang; Shijin Tian; Siran Peng (IET Renewable Power Generation)
Abstract With the increasing penetration rate of renewable energy in the power system, it becomes increasingly important to coordinate adequacy, flexibility, and environmental protection. The development of the power market provides diverse signals for power investors and plays an increasingly significant role in the decarbonization of the power system. However, due to the interdependent operations of various power markets, measuring the multifaceted value of power generation within traditional market mechanisms poses considerable challenges. Herein, a bi‐level optimization model is proposed to integrate the capacity remuneration mechanism (CRM), energy market (EM), and carbon emission trading (CET). The adequacy, flexibility, and environmental revenue expectations of different generation resources through synergistic transactions are derived using Lagrange multipliers. Furthermore, the bilevel optimization model is converted to its equivalent single‐level scheme based on the Karush–Kuhn–Tucker optimality conditions. Finally, several case studies are conducted to demonstrate the effectiveness of the proposed model, along with comparisons and sensitivity analyses to study the principles behind synergistic transactions and the impact of some key parameters.